Magnus wind turbine: the effect of sandpaper surface roughness on cylinder blades - Marzuki, Omar Faruqi; Mohd Rafie, Azmin Shakrine; Romli, Fairuz Izzuddin; Ahmad, Kamarul Arifin (Springer, 2018)
The Magnus wind turbine is an invention that uses rotating cylinders as blades to extract energy fromthe wind. This invention overcomes the limitation of operating a wind turbine at low wind speed conditions.However, research regarding the torque generated by enhancing the surface roughness of the Magnus windturbine is still lacking. Thus, the study aims to understand the effect of varied sandpaper surface roughnesses onthe Magnus wind turbine torque output. The approaches used are: experimentation using a 6 cylinders modelinside a wind tunnel for Magnus force comparison, a Magnus wind turbine model for torque performance andsmoke flow visualisation for boundary layer analysis. The results show that the torque coefficient producedby P40 sandpaper to smooth the surface roughness is 0.079–0.016, which is nearly a five times improvementin the torque coefficient. On the other hand, the tip speed ratio further increases from smooth to rough surfaceenhancement (0.057–0.147). This significant finding indicates that the Magnus wind turbine performance canbe further improved using sandpaper surface roughness.